2016
DOI: 10.3892/or.2016.4633
|View full text |Cite
|
Sign up to set email alerts
|

Secreted recombinant human IL-24 protein inhibits the proliferation of esophageal squamous cell carcinoma Eca-109 cells in vitro and in vivo

Abstract: Interleukin-24 (IL-24) displays cancer-specific apoptosis-inducing properties in a broad spectrum of human tumors without harmful effects on normal cells. The human IL-24 protein is secreted as a glycosylated protein and functions as a pro-Th1 cytokine and a potent antiangiogenic molecule. However, the function of secreted recombinant human IL-24 (srhIL-24) protein in esophageal squamous cell carcinoma (ESCC) cells has not been studied. In the present study, we prepared a stable site-specific-integrated cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
(60 reference statements)
1
8
0
Order By: Relevance
“…Pre-clinical evidence-Jiang et al first documented that MDA-7/IL-24 functions as a tumor suppressor in human melanoma and other cancer cells [8,10]. Subsequently, several research group both nationally and internationally investigated the functional role of MDA-7/IL-24 as an anti-cancer gene in multiple cancers (summarized in Table 1) including breast cancer [11,[73][74][75], prostate cancer [76][77][78], lung cancer [79,80], melanoma [81][82][83], malignant glioma [84][85][86], neuroblastoma [87], pancreatic cancer [88,89], esophageal squamous cell carcinoma [90], hepatocellular carcinoma [91,92], colorectal cancer [93][94][95], renal carcinoma [96], cervical cancer [97], ovarian cancer [98,99], osteosarcoma [100], and cancer of blood and lymphatics including leukemia, and lymphoma [101,102]. Many of the above-mentioned studies were initially confirmed using in vitro cells in culture and were subsequently translated into in vivo pre-clinical animal models using human tumor xenografts in immune incompetent mice.…”
Section: 32mentioning
confidence: 99%
“…Pre-clinical evidence-Jiang et al first documented that MDA-7/IL-24 functions as a tumor suppressor in human melanoma and other cancer cells [8,10]. Subsequently, several research group both nationally and internationally investigated the functional role of MDA-7/IL-24 as an anti-cancer gene in multiple cancers (summarized in Table 1) including breast cancer [11,[73][74][75], prostate cancer [76][77][78], lung cancer [79,80], melanoma [81][82][83], malignant glioma [84][85][86], neuroblastoma [87], pancreatic cancer [88,89], esophageal squamous cell carcinoma [90], hepatocellular carcinoma [91,92], colorectal cancer [93][94][95], renal carcinoma [96], cervical cancer [97], ovarian cancer [98,99], osteosarcoma [100], and cancer of blood and lymphatics including leukemia, and lymphoma [101,102]. Many of the above-mentioned studies were initially confirmed using in vitro cells in culture and were subsequently translated into in vivo pre-clinical animal models using human tumor xenografts in immune incompetent mice.…”
Section: 32mentioning
confidence: 99%
“…So far, researchers have confirmed that MDA-7/IL-24 is not only involved in normal immune function and wound healing, but it also has several additional beneficial effects in a variety of human diseases. As examples, MDA-7/IL-24 functions as an anticancer gene in multiple diverse cancers including melanoma (Lebedeva et al, 2002; Sarkar et al, 2008), prostate cancer (Greco et al, 2010; Lebedeva, Sarkar, et al, 2003; Lebedeva, Su, Sarkar, & Fisher, 2003), breast cancer (Bhutia et al, 2013; Menezes et al, 2015; Pradhan et al, 2017; Sarkar et al, 2005), osteosarcoma (Zhuo et al, 2017), neuroblastoma (Bhoopathi et al, 2016), pancreatic cancer (Sarkar, Quinn, Shen, Dent, et al, 2015), renal carcinoma (Park et al, 2009), leukemia (Rahmani et al, 2010), lung cancer (Lv, Su, Liang, Hu, & Yuan, 2016; Shapiro et al, 2016), esophageal squamous cell carcinoma (Ma, Jin, et al, 2016), and hepatocellular carcinoma (Wang, Ye, Zhong, Xiang, & Yang, 2007). MDA-7/IL-24 provides protection against autoimmune diseases and bacterial infections (Leng, Pan, Tao, & Ye, 2011; Ma et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of 5-FU on the proliferation of Eca-109 and Eca-109/5-FU cells in vivo was investigated by xenograft tumors in nude mice as previously described (36). All applicable international, national and/or institutional guidelines for the care and use of animals were followed.…”
Section: Evaluation Of Tumor Growth In Vivomentioning
confidence: 99%